2007
DOI: 10.1007/s11523-007-0048-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapies in head and neck cancer

Abstract: Over the past decade, the important role of different growth factors and their receptors and signal transduction pathways in the genesis and progression of tumors has been well recognized and their mechanism of action and interactions is gradually being unraveled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 142 publications
2
11
0
4
Order By: Relevance
“…The results were consistent with our previous results which depicted upregulation of MMP-2 and MMP-9 in oral cancer (Shrestha et al, 2014). Earlier studies have observed that MMP-9 expression was associated with tumor metastasis of oral squamous cell carcinoma (OSCC) Specenier et al, 2015). Bhairavi N. Vajaria, Kinjal R. Patel, Rasheedunnisa Begum, Franky D. Shah, Jayendra B. Patel, Geeta M. Joshi, and Prabhudas S. Patel / American Journal of Oral medicine (2017) Vol.…”
Section: Discussionsupporting
confidence: 93%
“…The results were consistent with our previous results which depicted upregulation of MMP-2 and MMP-9 in oral cancer (Shrestha et al, 2014). Earlier studies have observed that MMP-9 expression was associated with tumor metastasis of oral squamous cell carcinoma (OSCC) Specenier et al, 2015). Bhairavi N. Vajaria, Kinjal R. Patel, Rasheedunnisa Begum, Franky D. Shah, Jayendra B. Patel, Geeta M. Joshi, and Prabhudas S. Patel / American Journal of Oral medicine (2017) Vol.…”
Section: Discussionsupporting
confidence: 93%
“…Zalutumumab or panitumumab are just two clinically successful examples of monoclonal antibodies inhibiting EGFR [41]; they may provide promising new perspectives [24].…”
Section: Second-line Chemotherapy In Head and Neck Cancermentioning
confidence: 99%
“…Current trials show that induction chemotherapy using the triple combination followed by radiochemotherapy is more effective than radiochemotherapy based on cisplatin alone. However, this regime also shows high toxicity, particularly hematological toxicity.Targeted therapies are now providing new hope [3]. We are beginning to understand the role of growth factors, their receptors and signaling pathways in the cancer genesis and progression.…”
mentioning
confidence: 99%
“…Targeted therapies are now providing new hope [3]. We are beginning to understand the role of growth factors, their receptors and signaling pathways in the cancer genesis and progression.…”
mentioning
confidence: 99%